2004
DOI: 10.1186/1741-7007-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundFocal clusters of slow wave activity in the delta frequency range (1–4 Hz), as measured by magnetencephalography (MEG), are usually located in the vicinity of structural damage in the brain. Such oscillations are usually considered pathological and indicative of areas incapable of normal functioning owing to deafferentation from relevant input sources. In the present study we investigated the change in Delta Dipole Density in 28 patients with chronic aphasia (>12 months post onset) following cerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(55 citation statements)
references
References 30 publications
1
50
0
2
Order By: Relevance
“…RI was accompanied by a suppression of spontaneous oscillatory activity in the delta band (1.3e4.0 Hz) while no change was seen in controls, linking delta suppression with suppression of tinnitus (also see Adjamian et al, 2012). Because increased delta activity has been observed in tinnitus and other deafferentation syndromes (Weisz et al, 2005;De Jongh et al, 2003;Meinzer et al, 2004;Vieth et al, 1996) and has been linked by one report with increased gamma oscillations in the auditory cortex of tinnitus sufferers (Weisz et al, 2007), Kahlbrock and Weisz suggested that suppression of delta activity may be a prerequisite for attenuation of the tinnitus sensation after masking. The hypothesis advanced by Kahlbrock and Weisz (2008) to explain RI (normalization of neural network activity in auditory cortex by masking) is similar to the hypothesis proposed here (suppression of hypersynchrony in the TFR) to explain the increase in ASSR amplitude evoked by 5 kHz probes after masking in the tinnitus group probed at this frequency but not in their controls.…”
Section: Other Electrophysiological Responses In Tinnitus and Rimentioning
confidence: 94%
“…RI was accompanied by a suppression of spontaneous oscillatory activity in the delta band (1.3e4.0 Hz) while no change was seen in controls, linking delta suppression with suppression of tinnitus (also see Adjamian et al, 2012). Because increased delta activity has been observed in tinnitus and other deafferentation syndromes (Weisz et al, 2005;De Jongh et al, 2003;Meinzer et al, 2004;Vieth et al, 1996) and has been linked by one report with increased gamma oscillations in the auditory cortex of tinnitus sufferers (Weisz et al, 2007), Kahlbrock and Weisz suggested that suppression of delta activity may be a prerequisite for attenuation of the tinnitus sensation after masking. The hypothesis advanced by Kahlbrock and Weisz (2008) to explain RI (normalization of neural network activity in auditory cortex by masking) is similar to the hypothesis proposed here (suppression of hypersynchrony in the TFR) to explain the increase in ASSR amplitude evoked by 5 kHz probes after masking in the tinnitus group probed at this frequency but not in their controls.…”
Section: Other Electrophysiological Responses In Tinnitus and Rimentioning
confidence: 94%
“…The patient was tested before (pre) and after (post) a short-term intensive (experimental) language training (Constraint-Induced Aphasia Therapy, CIAT, Meinzer et al, 2005;Pulvermueller et al, 2001) that was accomplished in German. The development of CIAT has been guided by neuroscientific knowledge about cortical plasticity and includes a heavy training schedule (3 h/day on 10 consecutive workdays) within a motivating setting.…”
Section: Language Training and Testingmentioning
confidence: 99%
“…In a first fMRI scan, naming of visually presented objects was required in German and French in order to investigate cortical activation accompanying word-retrieval as a function of the long-term rehabilitation efforts. Then, the patient participated in a 2-week intensive (German) language training (Meinzer, Djundja, Barthel, Elbert, & Rockstroh, 2005;Pulvermueller et al, 2001). Special emphasis was given to word-retrieval in this training.…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic of neurons is the ability to form new connections and the more frequent neurons are active simultaneously, the stronger their connections become (Hebbian learning) (Kleim & Jones, 2008;Pulvermüller & Berthier, 2008). By increasing the intensity of impairment-based treatment, enhancement of neuronal connections can be achieved in the preferred left hemispheric lesional and perilesional areas in both the acute and chronic stage of stroke, and this has been related to a favourable outcome (Belin et al, 1996;Davis & Harrington, 2006;Fridriksson, Richardson, Fillmore, & Cai, 2012;Léger et al, 2002;Mattioli et al, 2014;Meinzer et al, 2004;Rochon et al, 2010).…”
Section: Introductionmentioning
confidence: 97%